Pre-Service EFL Teachers' Perception of Blended Learning - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
Due to its great prospects to maximize the advantages of both online learning and face-to-face learning, blended learning (BL) has been growing as one of the most important educational advances of the 21st century. Current studies have revealed that BL is very potential to help address students' diverse needs and learning styles, advance students' learning experience by developing their engagement, motivation, and capacity for reflection, and provide learners with direct experience with technology-supported skills essential for 21st-century success style. This study aimed at investigating the perception of pre-service EFL teachers of blended learning in learning English as a foreign language (EFL) setting. Employed a mixed methods research design, quantitative and qualitative data were collected from 32 students of the English Education Department of Universitas Kristen Indonesia Jakarta. The findings revealed that the students' perception of blended learning was positive. The participants also valued learning using the online platform not only because it offers convenience, flexibility, and immediate access but also increases their engagement and independence and develops their technical and information literacy skills. However, they viewed face-to-face instruction more effective for it is more realistic due to the presence of direct interaction, immediate response, and the convenience of reading printed texts.